A knight’s Life Between Love and Duty As Seen in Sir Walter Scott’s Ivanhoe - Melki Liswandi (Fakultas Sastra Universitas Ekasakti, 2017)
The problem in this thesis is the life of a knight who has to choose between duty and love. Dif analysis on the main task because on one side must perform his duties as a knight, and on the other side must follow his conscience to get his love. The problem of duty and love does not fit in the story. The purpose of this study is to evaluate the duties and responsibilities of the knight in performing his duty to the country where the knight is also confronted with his feelings and love, be a confrontation between the duty and responsibility to the knight. In this writing, literature research is taken as a method of data. As for the method of data analysis, the authors perform comparative procedures with the understanding of novels, figures, and also psychiatric theory. Technical techniques data data research results relevant to the research. In data analysis techniques, the author uses the technique of genetic structuralism by analyzing the knight in the Ivanhoe novel through psychic theory, the writer must see the confrontation that the knight must enter in choosing a task or love. The findings in this thesis are: 1) the knight prefers the task to fullness and prefers love in the end, 2) at the beginning of the story, the knight prefers to give priority to his duty to the king so that he is carried away Rowena, his beloved girl 3) At the end of the story, the knight returns to give priority to his love for Rowena.